Penggunaan Menstruation Tracking Wheel and Information terhadap Pengetahuan dalam Pemilihan Metode Kontrasepsi pada Wanita Usia Subur (WUS) - Indrayani, Neni; Aifa, Wira Ekdeni; Tanberika, Fajar Sari; Yanti, Rifa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the effect of using the Menstruation Tracking Wheel and Information on the knowledge of women of childbearing age (WUS) in choosing contraceptive methods in Hamlet 1, Kota Baru Village, Rakit Kulim District, Indragiri Hulu Regency. The method used was a quantitative study with a quasi-experimental design using a one-group pretest-posttest. The study sample consisted of women of childbearing age who received an intervention in the form of the use of the Menstruation Tracking Wheel and Information along with contraceptive education. Data were analyzed bivariately using the Wilcoxon signed rank test. The results of the study using the Wilcoxon signed rank test showed a p-value of 0.000 < 0.05. The conclusion of this study is that the use of the Menstruation Tracking Wheel and Information has an effect on increasing the knowledge of women of childbearing age in choosing contraceptive methods, thus making this media a potential tool for family planning education and counseling. Keywords: Contraception, Menstruation Tracking Wheel and Information, Knowledge, Women of Childbearing Age (WUS)